Optical Flow and Principal Component Analysis-Based Motion Detection in Outdoor Videos. (8th March 2010) - Liu Liu, Kui Kui; Du Du, Qian Qian; Yang Yang, He He; Ma Ma, Ben Ben
Abstract : We propose a joint optical flow and principal component analysis (PCA) method for motion detection. PCA is used to analyze optical flows so that major optical flows corresponding to moving objects in a local window can be better extracted. This joint approach can efficiently detect moving objects and more successfully suppress small turbulence. It is particularly useful for motion detection from outdoor videos with low quality. It can also effectively delineate moving objects in both static and dynamic background. Experimental results demonstrate that this approach outperforms other existing methods by extracting the moving objects more completely with lower false alarms.